Inequality in access to sanitation services in the Amazon: An analysis of the northern region (Desenvolvimento em Questão, 2025)
Access to basic sanitation services is essential for achieving health and quality of life for the population. However, according to the 2022 Demographic Census, Brazil still faces significant challenges in terms of the adequate provision of these services, especially in the North. In view of this, this study aimed to analyze the indicators for water supply, sewage disposal and waste collection in the northern region of the country in 2022. Using a descriptive approach, the research methodology employed secondary data from the National Household Sample Survey, made available by the Brazilian Institute of Geography and Statistics (IBGE). The results of the analysis revealed precariousness in all sanitation services throughout the northern region, especially in rural areas. The sociodemographic characteristics showed that inequalities in access were more pronounced among groups with lower levels of education and income, as well as among black, brown and indigenous people. The analysis highlights the need to increase investment and integrate public policies in order to increase the supply and universalization of sanitation, as provided for in the legal framework and the UN's 2030 Agenda.
Keywords: Water supply; sewage disposal; garbage collection; sociodemographic characteristics; Northern region